The approach to hyperglycemic emergencies - A focus on diabetic ketoacidosis and hyperglycemic hyperosmolar state (Research, Society and Development, 2024)
Introduction: Diabetes mellitus is a chronic disease characterized by difficulty in metabolizing glucose due to relative or absolute insulin deficiency leading to acute complications such as hyperglycemic emergencies. Objective: This study aims to review the main clinical characteristics of hyperglycemic emergencies, especially diabetic ketoacidosis and hyperglycemic hyperosmolar state, highlighting recent advances and scientific gaps. Materials and Methods: This is an integrative literature review on the clinical characteristics of diabetic ketoacidosis and hyperglycemic hyperosmolar state. The PICO strategy was used to develop the guiding question. In addition, the descriptors “Diabetic Ketoacidosis”; “Hyperglycemic Hyperosmolar State”; and “Propaedeutics” were cross-referenced in the databases with the greatest impact on the scientific community. Results and Discussion: The articles showed that the pathophysiological mechanisms of the two complications converge, mainly due to the link between plasma insulin levels and hyperglycemia. The clinical manifestations and the propaedeutic process vary at certain points, while the treatment of both follows a sequential pattern for resolving the condition. Conclusion: Hyperglycemic emergencies resulting from diabetes mellitus require rapid intervention, given the severity of the condition and the reserved prognosis without proper treatment.